"More Life, Not Less": Using Narrative Therapy With Older Adults With Bipolar Disorder. Issue 1 (April 2016) - Burgin, Emma C.; Gibbons, Melinda M.
Abstract : Counselors who work with older adults with bipolar disorder are in a unique position to help them navigate their challenges. Older adults with bipolar disorder have lived decades with mental illness and also face the regular aging process. Narrative therapy provides counselors with a framework to deal with these issues.